Comprehensive comparison of salivary gland and cutaneous adnexal tumors: analogous versus discrepant clinical, terminological, histological, and molecular features: Part II: Second series of related tumor entities and synoptic comparison of general aspects - Ihrler, Stephan; Greber, Lukas; Agaimy, Abbas; Haas, Christian; Jurmeister, Philipp; Böer-Auer, Almut (Virchows Archiv, 2026)
This publication presents in two parts a comprehensive comparison of the manyfold salivary gland and cutaneous adnexal tumors, investigating both striking similarities and discrepancies with respect to clinical aspects, terminology, (immune)-histology, and molecular pathology. Part I has presented basic embryology/histology and overlapping topographical aspects, followed by a first series of related tumor entities. In this second part, a further series of histologically analogous/similar tumor entities are compared, comprising secretory and microsecretory carcinoma, sialadenoma and syringocystadenoma papilliferum, adenoidcystic carcinoma, mucinous and mucoepidermoid tumors, lymphoepithelial tumors, sebaceous tumors, and further rare related tumor groups. Finally, in a synoptic comparison, general features are summarized: While tumors with follicular differentiation are lacking in salivary glands, tumors with acinar and oncocytic differentiation are lacking in the skin. In general, salivary tumors have a higher proportion of malignancy, are on average larger, are frequently more difficult to resect due to a more complex topography, and, hence, show a higher propensity for recurrence and metastases, on average with a poorer prognosis. Multifocality with or without link to hereditary tumor syndromes is not infrequent in cutaneous lesions, but is very rare in salivary tumors.
CRIS-Team Scopus Importer:2026-02-06
Keywords: Cutaneous adnexal; Histogenesis; Molecular pathology; Salivary gland; Terminology; Tumor